Electronic administrative procedure - Patrón Bedoya, Pedro (2018)
In Peru, as part of the implementation of electronic government, a process of incorporation of Information and Communication Technologies (ICTs) is being carried out so that citizens can relate to public administration entities. by electronic means to present writings, resources and complaints; make payments; receive notifications when this means is accepted or requested by the administrator; access general administrative information and files to know the status of them; avoid the repeated presentation of documents that are already in the hands of the public administration, among others.In Peru the legal conditions are being given to grant validity to the administrative procedure processed electronically. In this context, several provisions have been issued that modify Law N ° 27444, Law of General Administrative Procedure, establishing the legal framework for the use of electronic administrative procedures